E-Activity and Technology in a Changing Environment - Berchtold, Gerhard (Richtmann Publishing, 2012)
IntroductionThe second half of the last century will go down in the history of higher education as the period of its mostspectacular expansion: an over sixfold increase in student enrolments worldwide, from 13 million in 1960 to82 million in 1995. But it is also the period which has seen the gap between industrially developed, thedeveloping countries and in particular the least developed countries with regard to access and resources forhigher learning and research, already enormous, becoming even wider.